2018
DOI: 10.5194/esd-9-267-2018
|View full text |Cite
|
Sign up to set email alerts
|

Global drought and severe drought-affected populations in 1.5 and 2 °C warmer worlds

Abstract: Abstract. The 2015 Paris Agreement proposed a more ambitious climate change mitigation target on limiting global warming to 1.5 • C instead of 2 • C above preindustrial levels. Scientific investigations on environmental risks associated with these warming targets are necessary to inform climate policymaking. Based on the Coupled Model Intercomparison Project phase 5 (CMIP5) climate models, we present the first risk-based assessment of changes in global drought and the impact of severe drought on populations fr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
115
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 153 publications
(133 citation statements)
references
References 51 publications
10
115
0
Order By: Relevance
“…The significant warming trend of the UMHRB in the future is consistent with the conclusion pointed out by Liu et al [18] describing that the temperature warming continues to rise at a high level.…”
Section: Changes Of Annual and Seasonal Temperature Historically And supporting
confidence: 91%
See 1 more Smart Citation
“…The significant warming trend of the UMHRB in the future is consistent with the conclusion pointed out by Liu et al [18] describing that the temperature warming continues to rise at a high level.…”
Section: Changes Of Annual and Seasonal Temperature Historically And supporting
confidence: 91%
“…Dai [17] has found that the global aridity has increased substantially since the 1970s and the climate models project increased aridity in the 21st century over most of Africa, southern Europe, the Middle East, most of the American continent, Australia, and Southeast Asia. Liu et al [18] revealed that there would be an increasing drought risk if the global warming continues to rise at a high level. Ahmadalipour et al [9] took an ensemble of 10 regional climate models and a multi-scalar drought index to quantify drought hazard and found that drought risk in Africa is expected to increase in future with varied rates for different models and scenarios.…”
mentioning
confidence: 99%
“…This study determined assessment methods from different sources of climate change risk: (1) Sudden onset events, that is, extreme weather/climate events, which occur within a short period of time and are associated with hazards and adverse consequences. Climate change factors are equivalent to disaster‐causing factors (risk‐causing factors) in natural disasters (Li et al, ; Liu et al, ). (2) Slow onset events, which occur when system indicators exceed certain thresholds, causing adverse effects and risks (Rosenzweig et al, ; Yin et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Even if the nationally determined contributions promised in the Paris Agreement are completely realized, the GMST would increase to 2.8 °C above preindustrial levels by 2100 (Climate Action Tracker, ; Raftery et al, ). In the context of climate change, the intensity and frequency of extreme climate‐related events (e.g., droughts, heat waves, and floods) would increase rapidly and nonlinearly, with increasingly severe impacts (Donnelly et al, ; Fischer & Knutti, ; Liu et al, ). The frequency of extreme high temperatures under a GMST increase of 2.0 °C is almost double that under an increase of 1.5 °C and more than 5 times higher than for present conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Since then few studies have conducted numerical experiments (e.g. Mitchell et al 2017) and investigated global (Mitchell et al 2016, Liu et al 2018 and regional (King et al 2017, Chevuturi et al 2018 impacts of 1.5°C warming as well as an additional half degree warming to 2°C. However, the short-term interest among the signatory countries, technological lock-ins in energy systems and socio-economic constraints questions the feasibility of such an objective.…”
Section: Introductionmentioning
confidence: 99%